(untitled) - Michael C Latham (Rome, 1997)
This book provides sound science-based information on food, nutrients, the cause of malnutrition, nutrition disorders and their prevention. The information can be used by workers in the field and disseminated to assit the public in marking informed food choices and appropriate decisions about diet. The publication will be especially useful for those working rural populations.
Keywords: developing counties,food supply,human nutrition